Strategies and Steps Taken by Tourism Stakeholders to Communicate Urban Tourism Promotions to Generation Z in Jakarta - Linda RM Gurning; Marta Eriska; Friska Nurlina Sirait; Irene Hasian; Putu Swasti Asparini (Institut Pariwisata Trisakti, 2026)
Urban tourism in Jakarta faces both challenges and opportunities in attracting Gen Z as potential domestic tourists. This study proposes promotional strategies based on the strategic steps taken by tourism stakeholders in communicating urban tourism promotions to Gen Z. This study employs a qualitative approach using the design thinking method through five stages: empathize, define, ideate, prototype, and test. Data were collected through observation, semi-structured interviews, and literature review. The results indicate that stakeholders adopt three main approaches: (1) strengthening their role through digital ecosystems, culturally informed policies, and creative public spaces; (2) leveraging technological innovations such as Augmented Reality/Virtual Reality, gamification, and interactive social media content; and (3) promotion strategies based on community engagement, digital accessibility, and cross-sector collaboration. These findings underscore that the integration of technology, creativity, and participatory approaches is key to building an emotional connection with Gen Z and strengthening Jakarta’s position as an urban tourism destination relevant to the lifestyle of the younger generation. Kata kunci : Gen Z, urban tourism, design thinking, gamification